2019
DOI: 10.1248/cpb.c18-00890
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Adhesive Properties to Identify Cohesive and Dispersive Ophthalmic Viscosurgical Devices

Abstract: The purpose of this study is to evaluate the usefulness of the rheological properties and adhesive force of ophthalmic viscosurgical devices (OVDs) as parameters for understanding and identifying the surgical behavior of cohesive and dispersive OVDs. The apparent viscosity, and the storage and loss moduli (dynamic rheological parameters) of 50% chondroitin sulfate (CS), 3% sodium hyaluronate (HA), Shellgan (the combination of 3% HA and 4% CS), Opegan (1% HA with a low molecular mass) and Opegan-Hi (1% HA with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…We previously reported that the OVDs tested in this study had specific rheological properties even when they were of the same composition or classification type [14,15]. Here, we clarified the advantages and disadvantages of each OVD for the wet shell technique on the basis of their properties.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…We previously reported that the OVDs tested in this study had specific rheological properties even when they were of the same composition or classification type [14,15]. Here, we clarified the advantages and disadvantages of each OVD for the wet shell technique on the basis of their properties.…”
Section: Discussionmentioning
confidence: 69%
“…In this study, Opelead, Viscoat, and Shellgan were classified into such a category ( Table 2). We previously evaluated the physical properties of these OVD products and demonstrated that their basic properties were different even though they belonged to the same category [14,15]. We have speculated that the molecular weight (Mw) and concentration of HA, which is the main component of OVDs, have a great influence on rheological properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency Response of Storage Modulus G′ (a), Loss Modulus G″(b), and tand (c)• Opegan-Hi; Hyaluronic acid``TEVA''; * Hyaluronic acid``Kowa''; ▲ Provisc; -Hyaguard; ◆ Opelead-HV; ■ Healon; × Opelead; + Opegan. These rheological parameters of Opegan, Provisc and Opegan-Hi have already been determined 14). …”
mentioning
confidence: 99%
“…† Information on the package insert of each OVD product as of March 2019. ‡ Mw of Opegan, Provisc and Opegan-Hi have already been determined 14). …”
mentioning
confidence: 99%